Analisis biomekanika menggunakan aplikasi kinovea terhadap aklselerasi lari 100 meter - Husni Tamim, Muhammad; Hariadi, Hariadi; Jumesam, Jumesam; Nopiana, Rina; Fathoni, Ahmad; Zulkarnain, Lalu Iskandar (Universitas Hamzanwadi, 2024)
The purpose of the researchers was to analyze students' 100-meter sprints using the Kinovea software application. This research was conducted to determine students' 100-meter sprint acceleration. This type of research is a quantitative descriptive analysis with a total of 6 subjects, consisting of 5 students and 1 comparison athlete. The results in this study NW Tebaban high school students can perform the highest 100 meter speed above 9 meters/second of 16.70% (1 runner), above 8 meters/second 0% (0 runners), 7-8 meters/second 33.30 % (2 runners), and those who can do an average speed of 100 meters 6-7 meters/second 50% (1 runner). NW SMA students. The number of runners who got in the very good category was 1 person with a percentage of 16.70%, the number of runners who got in the good category was 0 with a percentage of 0%, the number of runners who got in the fair category was 2 people with a percentage of 33.30%, the number runners who got less category amounted to 3 people with a percentage of 50% and the number of runners who got less category amounted to 0 with a percentage of 0%. In conclusion, NW Tebaban high school students are able to accelerate the 100 meter run with a percentage of 100% (6 people)